2014
DOI: 10.1021/la503362t
|View full text |Cite
|
Sign up to set email alerts
|

Study of Model Superoleophobic Surfaces Fabricated with a Modified Bosch Etch Method

Abstract: A set of surfaces featuring pillars with overhanging cap structures, exhibiting superoleophobic behavior, were fabricated using a new method. While such structures have been previously reported, in contrast with previous literature this new method allows for the control of pillar cross-sectional diameter, pillar separation, and Cassie fraction independent from the pillar radius-to-height ratio. Once fabricated the contact angles of the surfaces were examined using water, ethylene glycol, and hexadecane. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In the literature, it was shown that surface topographies with reentrant curvatures or multivalued roughness such as mushroom-like structures or overhangs can produce superoleophobic properties. [5][6][7][8][9][10][11] Here, we show that different surface morphologies can lead to superoleophobic properties but the presence of thin fi bers allow to reach such properties even if the roughness is low ( R a ≈ 0.2 µm) while higher roughness are necessary with spherical particles ( R a ≈ 2 µm).…”
Section: Discussionmentioning
confidence: 94%
“…In the literature, it was shown that surface topographies with reentrant curvatures or multivalued roughness such as mushroom-like structures or overhangs can produce superoleophobic properties. [5][6][7][8][9][10][11] Here, we show that different surface morphologies can lead to superoleophobic properties but the presence of thin fi bers allow to reach such properties even if the roughness is low ( R a ≈ 0.2 µm) while higher roughness are necessary with spherical particles ( R a ≈ 2 µm).…”
Section: Discussionmentioning
confidence: 94%
“…This framework is very useful since it gives theoretical validity to the experimentally confirmed practice of cosine averaging of measured advancing and receding contact angles to estimate the Young contact angle for smooth surfaces and explains why cosine averaging should never be used for rough surfaces. 63 As well, the framework is able to provide an explanation for a wide variety of seemingly inexplicable experimental results for contact angles on rough hydrophobic, 63 wetting, 65 and oleophobic 64 surfaces. The framework also allows one to gain additional insight into contact angle phenomena by comparing the magnitude of the extra surface forces between different experimental circumstances.…”
Section: Explanation For the Anomalously High Contact Angle Of Surfacmentioning
confidence: 95%
“…64 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 25 angles. It is important to understand that a surface force determined in this way would empirically account for all phenomena that cause advancing and receding contact angles to be different from thermodynamic equilibrium contact angles, and could be a frictional or pinning force, but could also include effects left out of thermodynamics such as disjoining forces arising from molecular interactions between interfaces, non-equilibrium redistribution effects in the case of surfactants, and local geometric constraints on contact angle in...…”
Section: Explanation For the Anomalously High Contact Angle Of Surfacmentioning
confidence: 99%
See 1 more Smart Citation
“…The gradient substrate was placed on a hotplate before it was placed horizontally. The measurements of CA were taken with the help of a high-speed camera (I-speed LT, Olympus, Tokyo, Japan), which was mounted by a support and adjusted horizontally to match the surface of substrate [ 41 , 42 ]. The morphology of how the droplet initially contacted the surface was recorded.…”
Section: Resultsmentioning
confidence: 99%